Analysis and Management of Complications in a Cohort of 1, 065 Minimally Invasive Cochlear Implantations. Issue 3 (March 2017) - Jiang, Yi; Gu, Ping; Li, Beicheng; Gao, Xue; Sun, Baochun; Song, Yueshuai; Wang, Guojian; Yuan, Yongyi; Wang, Cuicui; Liu, Miao; Han, Dongyi; Dai, Pu
Abstract : Objectives: To analyze complications associated with minimally invasive cochlear implantation by comparing data from different centers, to discuss major reasons for complications, and to refine implantation techniques to decrease them. Patients: Patients who underwent cochlear implantation at our center by the same surgeon (the corresponding author of this article) from March 2006 to March 2015 were enrolled. Intervention: First, a retrospective analysis of the complications associated with minimally invasive cochlear implantation at our center was performed. Second, published reports from other centers that describe complications were reviewed. Differences between complications in our cohort and other studies were evaluated. Main Outcome Measure: Strategies for reducing complications were assessed and modifications in surgical protocol proposed accordingly. Results: In total, 1, 014 patients underwent 1, 065 cochlear implantations. There were 28 complications (7 major, 21 minor) and only 2 reimplantations for the entire cohort, with no case of severe infection, flap necrosis, or device extrusion. The major complications were electrode misplacement, magnet displacement, implant failure secondary to trauma, and temporary cerebrospinal fluid leakage. The rates of major complications in our cohort were very low (0.6%) compared with those in the literature. Conclusion: Preoperative surgical planning based on individual patient anatomy and employment of soft surgical techniques can minimize surgical complications. Abstract : Supplemental Digital Content is available in the text